2007
DOI: 10.1093/gerona/62.6.616
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Resistance and Task-Specific Exercise in Older Adults Who Modify Tasks of Everyday Life

Abstract: The benefits of exercise are dependent on tasks performed during training. Exercise recommendations for low-functioning older adults should reflect task-specific exercise to prevent the onset of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
114
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 21 publications
4
114
2
1
Order By: Relevance
“…Three trials recruited older adults from either congregate housing or long-term care facilities [17,1,31]. Five studies specifically recruited older adults with some degree of difficulty or dependency in mobility or ADL [1,31,35,47,18]. Three trials exclusively recruited women [9,47,11].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three trials recruited older adults from either congregate housing or long-term care facilities [17,1,31]. Five studies specifically recruited older adults with some degree of difficulty or dependency in mobility or ADL [1,31,35,47,18]. Three trials exclusively recruited women [9,47,11].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six trials applied a two-group randomized controlled trial design: three trials compared functional training to an attention placebo control group [17,31,18]; one trial compared functional training to a control group who engaged in flexibility exercises [1]; one trial compared two programs that differed in functional training dosage, home exercise versus combined home and group exercise [21]; and one trial compared functional training to strength training [28]. Among three trials that applied a three-group randomized controlled trial design, in addition to a functional training group: two trials included a strength training group [35,11]; two trials included a control group [11,8]; one trial included a strength plus functional training group [35]; and one trial included a strength plus balance training group [8].…”
Section: Cohort Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies considered in this review showed positive effects of movements of everyday life in combination with balance exercises (Alfieri et al 2010;Egerton et al 2009;Mayer et al 2011). However, studies that implemented traditional resistance training without any additional exercises also displayed comparable positive effects (Aagaard et al 2010;Barry and Carson 2004;Bottaro et al 2007;Manini et al 2007). So it remains still unclear which training program is the most effective one for movements in everyday life.…”
mentioning
confidence: 99%